Analyzing the practice of South Korea’s public diplomacy in Indonesia: An approach with communication pyramid of public diplomacy - Vita Fitria; Haekal Adha Al Giffari; Daffa Al Falah; Muhammad Zul Razin (Journal of Social Studies (JSS), 2021)
The dissemination of South Korean culture in Indonesia becomes prominent as it attracts lot of people and creates many fans. The penetration of its spread in Indonesia is supported by some institutions which emphasizes on advocating and developing the South Korean culture and practice. The phenomena are not incidentally occurred, but it is well-managed by the government of South Korea as the advocate country of public diplomacy in collaboration with the target country which is Indonesia in achieving this mission. Public diplomacy is positioned as an approach of the advocate country to influence the public of foreign country to support the advocate’s country position which can be implemented through their state and non-sate actors in achieving mutual benefits. This paper observes the practice, impact, and challenges of South Korea’s public diplomacy in Indonesia based on Communication Pyramid Public Diplomacy framework. The findings show that the practice of public diplomacy allows cultural hybridity and increase enthusiasm of Indonesian in understanding the culture of the advocate country while the challenge is asymmetric direction between state and non-state actors of South Korea in the implementation of public diplomacy.